Cost-Effectiveness of Bariatric Surgery in Patients Living with Obesity and Type 2 Diabetes - Gábor Kovács; Elemér Mohos; János Tibor Kis; Ádám Tabák; Péter Gerendy; Judit Pettkó; Dávid Nagy; Dávid Győrbíró; Zoltán Kaló (Journal of Diabetes Research)
Aims. The favourable effects of bariatric surgeries on body weight reduction and glucose control have been demonstrated in several studies. Additionally, the cost-effectiveness of bariatric surgeries has been confirmed in several analyses. The aim of the current analysis was to demonstrate the cost-effectiveness of bariatric surgeries in obese patients with type 2 diabetes in Hungary compared to conventional diabetes treatments based on economic modelling of published clinical trial results. Materials and Methods. Patients entered the simulation model at the age of 45 with body mass index BMI≥30 kg/m2 and type 2 diabetes. The model was performed from the public payer’s perspective, comparing sleeve gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB) procedures to conventional care of diabetes. The results were provided separately for three BMI categories. Results. The base-case analysis demonstrated that both surgery types were dominant; i.e., they saved 17 064 to 24 384 Euro public payer expenditures and resulted in improved health outcomes (1.36 to 1.50 quality-adjusted life years gain (QALY)) in the three BMI categories. Bariatric surgeries extended the life expectancy and the disease-free survival times of all the investigated diabetes complications. All the scenario analyses confirmed the robustness of the base-case analysis, such that bariatric surgeries remained dominant compared to conventional diabetes treatments. Conclusion. The results of this cost-effectiveness analysis highlight the importance of bariatric surgeries as alternatives to conventional diabetes treatments in the obese population. Therefore, it is strongly recommended that a wider population has access to these surgeries in Hungary.